Réponses

2014-03-06T17:49:16+01:00
Bonsoir

(-4x+5)(3+2x)=0
soit -4x +5 = 0
-4x = -5
x = 5/4
soit 3+2x = 0
2x = -3
x = -3/2


4x²-81=0
(2x -9)(2x+9) = 0
soit 2x -9= 0
2x = 9
x = 4.5
soit 2x +9 = 0
2x = -9
x = -4.5

5x²=3x
5x² -3x = 0
x(5 x -3) = 0
soit x = 0
soit 5x -3 = 0
5x = 3
x = 3/5

(x-1)(-2x+3)-2(x-1)²=0
(x-1)(-2x+3 -2(x-1) =0
(x-1)(-2x +3 -2x +1) = 0
(x-1)(-4x +4) = 0
soit
x-1 = 0 et x = 1
soit -4x +4 = 0
-4x = -4
x = 1

(x-3)²=(5x+2)²
(x-3)² - (5x+2)² = 0
(x-3 +5x +2)(x-3 -5x-2) = 0
(6x -1)(-4x -5) = 0
soit 6x -1 = 0
6x = 1
x = 1/6
soit -4x -5 = 0
-4x = 5
x = -5/4